Greek Sport and Social Status - Golden, Mark (University of Texas Press, 2021)
From the ancient Olympic games to the World Series and the World Cup, athletic achievement has always conferred social status. In this collection of essays, a noted authority on ancient sport discusses how Greek sport has been used to claim and enhance social status, both in antiquity and in modern times. Mark Golden explores a variety of ways in which sport provided a route to social status. In the first essay, he explains how elite horsemen and athletes tried to ignore the important roles that jockeys, drivers, and trainers played in their victories, as well as how female owners tried to rank their equestrian achievements above those of men and other women. In the next essay, Golden looks at the varied contributions that slaves made to sport, despite its use as a marker of free, Greek status. In the third essay, he evaluates the claims made by gladiators in the Greek east that they be regarded as high-status athletes and asserts that gladiatorial spectacle is much more like Greek sport than scholars today usually admit. In the final essay, Golden critiques the accepted accounts of ancient and modern Olympic history, arguing that attempts to raise the status of the modern games by stressing their links to the ancient ones are misleading. He concludes that the contemporary movement to call a truce in world conflicts during the Olympics is likewise based on misunderstandings of ancient Greek traditions